IMPLEMENTASI GOOD GOVERNANCE PADA PEMERINTAHAN NAGARI DI SUMATERA BARAT - Malau, Hasbullah (TINGKAP, 2013)
One of the important issues in the contemporary world on post-modren era include the claims against the openness of the state and the ability of the government to involve the community. In order for the state and the government is able to meet the demands of the society, the country and the government should reform its public administration to become more democratic, efficient, and creating procedures for good governance and good local governance. Implementation of good governance for the regional administration based on local wisdom as a goal of governance will provide color of the ultimate goal of autonomy and participation as well as empowerment of communities in the implementation of regional autonomy. Keywords: good governance, otonomi daerah dan local wisdom